Commentary on the special edition on developments in field theory of the European journal of psychotherapy & counselling fields, systems, and silos: From electromechanics to the matrix. Issue 1 (2nd January 2022) - Penna, Carla; Hopper, Earl
ABSTRACT: This invited commentary on the editorial and the five articles that comprise the Special Edition on Field Theory, organized by the Guest Editors Richard Morgan-Jones and Robert Snell, discusses the importance of Kurt Lewin's concept of the social field and the confluence of Bion's and the Baranger's theories for the creation of contemporary field theory in psychoanalysis and Foulkesian group analysis. These disciplines share a kind of 'field paradigm', which is grounded in the axioms of the intrinsic relationality of human beings, which have become essential in psychoanalysis and group analysis both in theory and practice.